ANALISIS DAMPAK PENGELOLAAN DANA DESA TERADAP PEMBERDAYAAN MASYARAKAT DI KECAMATAN MAGETAN KABUPATEN MAGETAN - Wulan Agustiningrum; Isharijadi Isharijadi; Liana Vivin Wihartanti (UNIVERSITAS MUHAMMADIYAH METRO, 2020)
This research is related to the management of Village Funds in Magetan District, Magetan Regency which focuses on the impact of Village Fund management on community empowerment. This study aims to examine the management of Village Funds and how it impacts in the field of community empowerment in Magetan District, Magetan Regency, fiscal year 2019. The type of research used is qualitative with a descriptive approach. The results of this study show that the management of the Village Fund in the 2019 fiscal year is managed in accordance with applicable regulations. The impact of the Village Fund on community empowerment is that it has a